1982
DOI: 10.1021/ja00387a030
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear copper(II) cryptates of macrocyclic ligands: synthesis, crystal structure, and magnetic properties. Mechanism of the exchange interaction through bridging azido ligands

Abstract: The tetraazido dinuclear Cu(II) complexes 1 and 2 of the polyaza-polyoxa macrocyclic ligands 4, [24]ane-N2Oe, and 5, [24]ane-N602, respectively, have been prepared, and their crystal structures have been determined. In both cases the two copper ions are contained inside the molecular cavity and are bound to the ONO and NNN chelating subunits situated at the two poles of the macrocycles 4 and 5, respectively. 1 crystallizes in the monoclinic system, space group P2\/n (a = Dihedral Angles N(l)-C(2)-C(3)-0(4) 59.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
109
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(117 citation statements)
references
References 1 publication
7
109
0
1
Order By: Relevance
“…[1,2] In an effort to be concise, this work is restricted to the study of azido double-bridge copper(II) dinuclear systems. In these systems, the azido groups bridge the copper(II) ions either through one terminal nitrogen atom (m-1,1), in a socalled end-on coordination mode (abbreviated hereafter EO), [3][4][5][6][7][8][9][10][11][12][13][14][15][16] or through two terminal nitrogen atoms (m-1,3) in an end-to-end coordination mode (EE) as shown in Scheme 1. [11,[17][18][19][20][21][22][23] For both EO and EE systems, the bridge may be either symmetric (Scheme 1 a), when the two N À Cu bonds are Abstract: A new end-to-end azido double-bridged copper(II) complex [Cu 2 L 2 (N 3 ) 2 ] (1) was synthesized and characterized (L = 1,1,1-trifluoro-7-(dimethylamino)-4-methyl-5-aza-3-hepten-2-onato).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] In an effort to be concise, this work is restricted to the study of azido double-bridge copper(II) dinuclear systems. In these systems, the azido groups bridge the copper(II) ions either through one terminal nitrogen atom (m-1,1), in a socalled end-on coordination mode (abbreviated hereafter EO), [3][4][5][6][7][8][9][10][11][12][13][14][15][16] or through two terminal nitrogen atoms (m-1,3) in an end-to-end coordination mode (EE) as shown in Scheme 1. [11,[17][18][19][20][21][22][23] For both EO and EE systems, the bridge may be either symmetric (Scheme 1 a), when the two N À Cu bonds are Abstract: A new end-to-end azido double-bridged copper(II) complex [Cu 2 L 2 (N 3 ) 2 ] (1) was synthesized and characterized (L = 1,1,1-trifluoro-7-(dimethylamino)-4-methyl-5-aza-3-hepten-2-onato).…”
Section: Introductionmentioning
confidence: 99%
“…Some asymmetric EO systems [11][12][13] have now been found that exhibit antiferromagnetic Cu À Cu interactions, while several cases of ferromagnetic couplings have been reported for asymmetric EE systems. [11,22,23] In the early studies, [3][4][5][6][17][18][19][20] the symmetric EO coordination mode behavior seemed intrinsically ferromagnetic and independent of any structural parameters. This is why most previous theoretical studies focused on EO systems to explain such peculiar behavior, [24,[26][27][28][29][30] which was initially attributed to spin polarization effects.…”
mentioning
confidence: 99%
“…The macrocyclic Obisdien used was synthesized by a modification of the method previously described 5,6 . Zinc (II) nitrate hexahydrate (Zn(NO3)2.6H2O), magnesium(II) nitrate hexahydrate (Mg(NO3)2.6H2O), HCl, sodium sulfate, sodium selenite and sodium selenate, were reagents grade materials.…”
Section: Methodsmentioning
confidence: 99%
“…Great interest has been devoted to macrocyclic receptors containing in their framework both oxygen and nitrogen donor atoms 3,4 . Firstly synthesized by Lehn 5,6 and co-workers, the macrocyclic Obisdien has been studied as a ligand that form stables complexes with metal ions and anions 7,8 . Their capacity to form stable binuclear complexes with metal ions is remarkable.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical expression for the magnetic susceptibility of the dimer is then where the N, β, and k constants have their usual meanings. 13,14 The values of g, J, and θ parameters, determined by a leastsquares procedure, are g = 2.18, J = +13.2 cm -1 , and θ = -0.3 K.…”
mentioning
confidence: 99%